Short-run and long-run comovement of GDP and some expenditure aggregates in Germany, France and Italy - Thomas A. Knetsch (Deutsche Bundesbank, 2005)
The paper presents empirical work on short-run and long-run comovement between the German, French and Italian aggregates of private consumption, business investment, exports, imports, GDP, and changes in inventories. In country-specific data sets, cointegration analyses are carried out both to identify long-run economic relationships and to remove the trend components from the nonstationary series. Analytically, this is done by reparametrizing the vector error correction model in its common trends representation. The resulting (Beveridge-Nelson) trend and cycle components as well as the series of changes in inventories are analyzed with a focus on synchronicity. To measure crosscountry comovement at different frequencies, "cohesion", a summary statistic developed by Croux et al. [2001], is applied. Sampling variability and parameter uncertainty are captured by bootstrapped confidence intervals.
Keywords: E32; C32; 330; cointegration; trend-cycle decomposition; cohesion; bootstrap; Konjunkturzusammenhang; Sozialprodukt; Gesamtwirtschaftliche Nachfrage; Kointegration; Schätzung; Deutschland; Frankreich; Italien